Dolphins Encountered in Kepulauan Seribu - Yusli Wardiatno; Chikarista Irfangi; Totok Hestirianoto (Marine Science Department Diponegoro University, 2010)
Kepulauan Seribu has been considered as one of the dolphin migration routes. This is based on the number of reports from fishermen and communities in Kepulauan Seribu on the existence of cetacean. The purpose of this study was to assess the type, behavior, deployment location, and estimate the number of dolphins found in Kepulauan Seribu. Research was conducted on May 10th to May 27th, 2010 and 22nd June to 3 July 2010. Observations were made every day, except Friday, and started at 7:00 a.m. to 6:00 pm. Observation by boat was used in the research. Observation of the amount, type, and behavior of cetacean had been done visually. Based on research results, it can be concluded that the species of dolphins found in Kepulauan Seribu are Delphinus delphis, Pseudorca crassidens, Stenella longirostris, and Tursiops truncatus, with a total number of 145 individuals. Species of dolphins are most often found is T. truncatus, whereas the least common type is Delphinus delphis. In addition there are also calf and unidentified species. The location of the encounter with the dolphins most often occurs around Pulau Gosong Congkak (Karang Congkak) and Karang Lebar. Judging from the observed behavior, it can be said that Kepulauan Seribu is a foraging area and migration routes for cetacean. In addition, Kepulauan Seribu was also considered as nursery ground for calf. Key words : Cetacean, dolphin, Kepulauan Seribu Kepulauan Seribu diduga sebagai salah satu rute migrasi berbagai jenis lumba-lumba. Hal ini didasarkan pada jumlah laporan dari nelayan dan masyarakat di Kepulauan Seribu pada keberadaan lumba-lumba. Tujuan dari penelitian ini adalah untuk menilai jenis, perilaku, lokasi penyebaran, dan estimasi jumlah dan jenis Cetacean yang ditemukan di Kepulauan Seribu. Penelitian ini dilakukan pada 10-27Mei dan 22 Juni-3 Juli 2010. Pengamatan dilakukan setiap hari, kecuali hari Jumat, mulai jam 7:00-18:00. Penelitian ini menggunakan metode eksplorasi dengan menggunakan perahu motor. Pengamatan jenis, jumlah, dan perilaku lumba-lumba telah dilakukan secara visual. Berdasarkan hasil penelitian,dapat disimpulkan bahwa spesies lumba-lumba yang ditemukan di Kepulauan Seribu adalah Delphinus delphis, Pseudorca crassidens, Stenella longirostris, dan Tursiops truncatus, dengan jumlah total 145 individu. Spesies lumba-lumba yang paling sering ditemukan adalah T. truncatus, sedangkan tipe paling umum adalah Delphinus delphis. Selain itu ditemukan juga bayi lumba-lumba dan spesies yang tidak teridentifikasi. Lokasi perjumpaan dengan lumba-lumba paling sering terjadi di sekitar Pulau Gosong Congkak (Karang Congkak) dan Karang Lebar. Dilihat dari perilaku yang diamati, dapat dikatakan bahwa Kepulauan Seribu merupakan daerah mencari makan dan rute migrasi Cetacean. Selain itu, Kepulauan Seribu juga diduga sebagai daerah asuhan bagi bayi lumba-lumba. Kata kunci : Cetacean, lumba-lumba, Kepulauan Seribu